Knowledge and Self-Protective Practices Against COVID-19 Among Healthcare Workers in Vietnam - Nguyen, Anh Ngoc; Le, Xuan Thi Thanh; Ta, Nhung Thi Kim; Wong, Danny; Nguyen, Nguyen Thao Thi; Le, Huong Thi; Nguyen, Thao Thanh; Pham, Quan Thi; Nguyen, Quynh Thi; Duong, Quan Van; Luong, Anh Mai; Koh, David; et al. (Frontiers in Public Health, 2021)
Background. In middle-income countries like Vietnam, where healthcare resources are already constrained, protecting HCWs is essential to ensuring sustainability of Vietnam’s COVID-19 response. This study was conducted to assess knowledge and practices regarding the prevention of COVID-19 among HCWs in Vietnam to identify ways to disseminate information to maximize the safety of these essential workers. Methods. An online cross-sectional study, using respondent-driven sampling (RDS), was conducted in Vietnam. Exploratory factor analysis (EFA) was used to examine the validity of the questionnaire. Descriptive statistics, inferential statistics, and regression modeling were used to identify level of knowledge and practices among HCWs to prevent COVID-19 along with factors associated with those results. Results. Vietnamese HCWs had a moderately high level of knowledge with greater than 75% of participants demonstrating awareness of all modes of transmission aside from air. The mean knowledge score was 3.7±0.8 (range 1¬–5). Nearly all participants relied on the Ministry of Health (98.3%) and the internet (95.5%) for information regarding COVID-19. Participants endorsed a moderately high level of self-protective practices with mean scores of 4.2±0.6 and 3.6±0.6 for precautionary and psychologic measures, respectively. Nurses were more likely to practice precautionary measures than doctors, and HCWs at the central level were more likely to practice psychologic measures than those at district levels. Conclusion. Future education initiatives should consolidate the latest literature in an accessible format, focusing initially on gaps of knowledge regarding aerosol transmission. These initiatives should primarily focus on doctors, especially those in emergency and intensive care departments.